Detection of Zika Virus and Human Papilloma Virus in Cervical Cytology Samples using Two Real Time PCR Based Techniques in Ecuadorian Women diagnosed with ASCUS - Tobar, Pool; Vega, Marcela; Ordoñez, Cathy; Rivera, Lisette; Landivar, José; Zambrano, Héctor (Puerto Rico Health Sciences Journal, 2018)
Objective: Atypical Squamous Cells of Undetermined Significance(ASCUS) is the most reported result on pap smears. It is most commonly related to Human Papillomavirus (HPV) infections. However, other pathogens (EBV, Chlamydia) have been reported on cervical samples with abnormal results. Zika virus(ZIKV) has been found to induce cellular abnormalities on different tissues and its presence has been identified on genital secretions. Methods: Two real-time PCR has been made on cervical samples from the gynecological service of a third level hospital on Guayaquil-Ecuador. This work was part of a bigger study of ZIKV presence on different body fluids. Results: From 89 samples obtained, 19 received an ASCUS result. From these 5 were positive for ZIKV and 5 were positive for HPV, there were no co infections. Conclusion: Given the presence of ZIKV RNA and the absence of HPV DNA on cervical samples diagnosed as ASCUS, it might be plausible that ZIKV could be a triggering factor for the induction of cellular changes observed on these cells.